Said About Ibsen : by Norwegian writers - Ferguson, Robert (Norway : Gyldendal, 2006)
Language and Literature
2006\08\08
Keywords: Literature(Arts); Arts; Critical Appraisal; Norwegian Literature; Herrick Ibsen